RANCANG BANGUN SISTEM MONITORING KETINGGIAN AIR BERBASIS ANDROID MENGGUNAKAN TRANSISTOR WATER LEVEL SENSOR - Nyoman Arun Wiratama; Dewa Made Wiharta; Ni Made Ary Esta Dewi Wirastuti (Jurnal SPEKTRUM, 2020)
So far, controlling the water level in the dam is still done manually by utilizing humanoperators, where in this case there are often mistakes in making decisions. In this research, asolution is offered in the form of an Android-based Water Level Monitoring System Design usinga Water Level Sensor Transistor. There are 4 transistor water level sensors integrated withArduino, ESP8266 module, camera module, relay, automatic water faucet, and LCD. Eachsensor is used to determine the water level with 5 different states, namely Zero, Safe, Warning,Alert, and Danger. If the water level touches one of the sensors, the input given by the sensor willautomatically be processed by Arduino which will then trigger a relay to open / close the waterfaucet and the value and status of the water level will be displayed on the LCD. After that thecamera will take pictures of the water level then the ESP8266 module which functions to connectto an internet connection will help the tool to send water level data in the form of images, status,and water level values to the Android application and the Telegram application that have beeninstalled on the Smartphone. The results obtained from this study are the design of the waterlevel monitoring system can run well in accordance with expectations, but there are stilldeficiencies that can be overcome with several developments so that the design of the tool getsbetter results, for example by using a servo motor on the floodgate which later can make the toolwork system even better.